Selections from the skeletons under my eyelids: a memoir - Achey, Mary Katherine (Kansas State University, 2009)
At the age of 12, I developed a condition that caused me to hyperventilate, black out, and on occasion, experience horrific visions. Though the visions were sparse at first, they quickly increased in number as weeks progressed. In the eighth grade, they became a daily occurrence. Though at the time I knew there was something wrong with me, I had no idea what was causing my symptoms. Because the episodes caused many inconveniences and embarrassments, I withdrew from social activities and stopped attending school altogether. Believing that my problems were the result of a physical illness, my parents had my blood tested for diseases such as mononucleosis. I also underwent an MRI, which checked for any tumors or abnormalities in my brain. When all of my tests came back negative, I was referred to a psychiatrist. I told the psychiatrist about my inclination to avoid social activities, but refrained from telling her about the hallucinations. Despite my withheld information, she determined I had an extreme case of clinical depression and agoraphobia. Though I was comforted by the notion that I had been granted a diagnosis, I still found it impossible to leave my bedroom without having the strange episodes. As my symptoms of depression increased, my interest in living decreased. But with the help of family and close friends, I was able to persevere and accept my circumstances despite the discomfort they created in my world.
Keywords: depression; panic; memoir; adolescence; Health Sciences, Mental Health (0347)